2022
DOI: 10.1155/2022/4255554
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Diversity among Important Brinjal (Solanum melongena) Cultivars Using Morphological Markers

Abstract: Background. Solanum melongena is a medicinally important vegetable crop that belongs to the family Solanaceae, which is cultivated worldwide. Methodology. In the present study, 22 eggplant varieties from the different ecogeographical regions were evaluated for nine quantitative and twenty-two qualitative morphological characters. A significant divergence was observed in all characters and wide regional variations for plant characteristics, flower, and fruit characteristics. Principle component analysis (PCA) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 26 publications
0
5
0
5
Order By: Relevance
“…During environmental challenges like drought, plants often encounter reduced photosynthetic rates and chlorophyll degradation, leading to diminished growth and productivity. However, research indicates that applying phytosynthesized NPs can ameliorate these detrimental effects and enhance photosynthetic efficiency [1,2,185,[332][333][334].…”
Section: Stimulation Of Photosynthesis and Chlorophyll Contentmentioning
confidence: 99%
See 3 more Smart Citations
“…During environmental challenges like drought, plants often encounter reduced photosynthetic rates and chlorophyll degradation, leading to diminished growth and productivity. However, research indicates that applying phytosynthesized NPs can ameliorate these detrimental effects and enhance photosynthetic efficiency [1,2,185,[332][333][334].…”
Section: Stimulation Of Photosynthesis and Chlorophyll Contentmentioning
confidence: 99%
“…These nanoparticles, made from plant extracts, have the extraordinary potential to encourage plant growth, increase stress tolerance, and improve nutrient intake. We must examine numerous critical research paths and suggestions before profiting from these phyto-synthesized NPs in agriculture [185,332,386].…”
Section: Future Research Directions and Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Divya et al, (2020) conducted experiment on brinjal at under mid hill conditions of Himachal Pradesh and reported the plant height was 130.47 cm recorded in UHF -BRL -4 variety. Younas et al, (2022) concluded and reported that the plant height was 62.1 cm recorded in 004729 ( 01…”
Section: Introductionmentioning
confidence: 98%